2002
DOI: 10.1056/nejmoa010806
|View full text |Cite
|
Sign up to set email alerts
|

Low and Very Low Birth Weight in Infants Conceived with Use of Assisted Reproductive Technology

Abstract: The use of assisted reproductive technology accounts for a disproportionate number of low-birth-weight and very-low-birth-weight infants in the United States, in part because of absolute increases in multiple gestations and in part because of higher rates of low birth weight among singleton infants conceived with this technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
499
9
23

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 916 publications
(556 citation statements)
references
References 19 publications
25
499
9
23
Order By: Relevance
“…Currently the consequences of such treatments on the health of offspring remain controversial. However, several studies now suggest that pregnancies derived from IVF/ICSI result in babies who are at an increased risks of cerebral palsy [105], premature birth [106,107], low and very low birth weight [108], complications during delivery [109] and serious birth defects [110]. It is important however to note the controversy in the current literature, where opposing studies have found no association between the use of ART and various health outcome in children [111,112].…”
Section: Seminal Plasma and Assisted Reproductionmentioning
confidence: 99%
“…Currently the consequences of such treatments on the health of offspring remain controversial. However, several studies now suggest that pregnancies derived from IVF/ICSI result in babies who are at an increased risks of cerebral palsy [105], premature birth [106,107], low and very low birth weight [108], complications during delivery [109] and serious birth defects [110]. It is important however to note the controversy in the current literature, where opposing studies have found no association between the use of ART and various health outcome in children [111,112].…”
Section: Seminal Plasma and Assisted Reproductionmentioning
confidence: 99%
“…Some of the complications have been attributed to a higher frequency of multiple births and to the increased risk of premature delivery; however, other reports indicate that also singleton IVF children have a greater risk of low birth weight and of congenital anomalies [8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…While ART is an effective means of building a family in those for whom other treatments are unsuccessful, research geared towards defining those aspects of the treatment protocols associated with adverse outcomes continues. Some of the well-described adverse outcomes include multiple gestation, chromosomal abnormalities, birth defects, preterm delivery, small for gestational age/low birth weight infants, preeclampsia, placenta previa, cesarean delivery and perinatal morbidity [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%